Análisis de contenidos en Diario La Prensa de Riobamba, sobre la restauración del Teatro León. 2018 - 2020. - García Vinueza, Viviana Jacqueline (2022)
The subsequent research entitled "Content analysis in La Prensa de Riobamba newspaper, about the restoration of the Leon Theater in 2018 - 2020" was carried out to do a content analysis on the restoration of the Leon theater in the printed media La Prensa. This research was done to understand the creation and distribution of informative content. For the development of this research, the methods we worked with were: field research; we used this method because we went to the municipal library and the facilities of La Prensa newspaper, to be able to find the newspapers of the years 2018, 2019, and 2020. We use the method of quantitative-qualitative, documentary research. It was non-experimental research because the phenomena were observed as they appeared in their natural context. Documentary review, content analysis, and interview techniques were used. The Content analysis matrix instrument was structured by: note number, date, headline, code, journalist, section, theme, gender, page, location, summary, and graphic help was applied. Thirty-two notes were analyzed in the three years reviewed, where much data about Leon theater was found. Most of the notes use the journalistic genre, of the informative note, in none of the reviewed notes was found any interview that has been carried out during the restoration. During the interview with the deputy director of La Prensa newspaper, it was mentioned that there was no specialized communicator in cultural heritage involved. A "Manual for the management of heritage content in print" reinforces the logic that exists in publications in print media to take advantage of the given tools and better manage information on cultural heritage.